Transformative Learning Media for Generation Z: Integrating Moral Values through Interactive E-Books in Islamic Education - Yumna Yumna; Hambali Jaili; Preexcy B. Tupas; Nana Fauzana Azima; Minsih Minsih; Dina Dahliana; Nadia Fransiska (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2024)
Recent developments in educational media have neglected certain key subjects, especially Akidah Akhlak, which is an essential part of the Madrasah Ibtidaiyah curriculum. The conventional learning resources, primarily textbooks, face several challenges that lead to a decline in students' interest in reading and engaging with the material. To address this issue, a focused initiative has been undertaken to create educational media that incorporates stories rich in moral lessons, with the goal of creating a more dynamic and engaging learning atmosphere. The advanced technological skills and information literacy of Generation Z children make a strong argument for the integration of digital textbooks, specifically e-books, into their education. This research seeks to lead the way in developing innovative learning tools that encourage children to actively engage with digital books powered by information technology. Utilizing a research and development methodology, the main goal is to explore the effectiveness of interactive e-books as powerful educational tools for children. These e-books are crafted to present information in a way that is easily understood and retained by young learners, thus positively impacting their cognitive and emotional development. The impressive effectiveness of Akidah Akhlak e-books designed for 2nd-grade students in Madrasah Ibtidaiyah highlights their success in improving educational outcomes. By weaving moral values into engaging stories, these e-books not only enhance knowledge retention but also promote the growth of key character traits and ethical values. This highlights the powerful impact of interactive e-books as essential tools in contemporary education, meeting the varied learning needs and preferences of today's digitally inclined students.